A NARRATIVE INQUIRY OF ENGLISH FOR YOUNG LEARNERS TEACHERS PROFESSIONAL IDENTITY CONSTRUCTION - Hanifia Arlinda; Safrina Noorman; Yanty Wirza (Universitas Pendidikan Indonesia, 2020)
This study aims at investigating the process of shaping teacher professional identity of English for Young Learners (EYL) teachers in elementary schools in Indonesia. This study also conducted to find out how the teachers reflect on their professional identity into their teaching practice. Employing narrative approach, this study focused on the narration of two participants’ stories, a male and a female novice teacher, on how their professional identity was constructed in the beginning of their career as EYL teachers. Semi-structured online interviews, photovoice and online classroom observation were administered to the participants in order to collect the data. The results suggest that participants’ teacher professional identity (TPI) was shaped by their significant life events, experiences in education, and interactions with students. Furthermore, this study has demonstrated a strong relationship between how teachers develop their professional identity and their belief about teaching EYL. Pedagogical implications of this study are also presented in this article. Keywords: English for Young Learners (EYL), teacher Identity, Teacher Professional Identity (TPI), narrative inquiry.